Development of a Distributed Water Stress Model for Karuvannur River Basin. (2016) - Sreelekshmi, J.; Thomas, Reeba
Abstract: Water stress is a situation where the availability of water is a major constraint on growing water demands. In this study the water stress status of Karuvannur River Basin (KRB) is assessed in a distributed scale. It is computed on the basis of a factor called stress ratio expressed as the ratio of water demand and water availability. Therefore, connecting the quantity of water demand with the amount available can shed light to the status of the water resource and the need for further corrective action. In this study, the water stress analysis is carried out both in basin and sub-basin scale. For that, the Karuvannur river basin is divided into 11 sub-basins and their water availability is assessed based on long term rainfall-runoff simulation using Soil Water Assessment Tool (SWAT). The water availability of the basin is computed by analyzing historical data. By conducting frequency analysis, the total available water is taken as the discharge that equalled or exceeded 95% of the time. The water demand is calculated considering the domestic requirement alone. It is seen that though total available water is more than enough to meet the domestic demand of water at basin scale, water scarcity in certain areas got exposed only when the analysis is done on a sub-basin level and to a monthly time scale. Since water is sufficiently available within this basin, by implementing conservation measures within the basin, such problems can be solved. These results may also assist in planning of future water resources development and reducing the water crisis that may prevail in Karuvannur river basin due to water scarcity.